Significant Changes in the Skin Microbiome in Patients with Chronic Plaque Psoriasis after Treatment with Narrowband Ultraviolet B - Malin Assarsson; Albert Duvetorp; Olaf Dienus; Jan Söderman; Oliver Seifert (Medical Journals Sweden, 2018)
Changes in the skin microbiome have been shown to promote cutaneous inflammation. The skin microbiome of patients with chronic plaque type psoriasis was analysed before and after treatment with narrowband ultraviolet B (UVB). Swab samples of the microbiome were taken from lesional and non-lesional skin of 26 patients. Microbiotas were characterized by sequencing 16S rRNA bacterial genes on the Illumina MiSeq platform. Lesional skin microbiome diversity correlated with psoriasis severity (measured with the Psoriasis Area and Severity Index; PASI). There was a significantly lower abundance of the phylum Firmicutes and the genus Staphylococcus in lesional skin compared with non-lesional skin before UVB treatment. Responders (> 75% target Psoriasis Severity Index (PSI) improvement) had significantly lower abundance of the phyla Firmicutes in lesional and non-lesional skin and lower abundance of the genera Staphylococcus, Finegoldia, Anaerococcus, Peptoniphilus, Gardnerella, Prevotella and Clostridium in lesional skin after UVB treatment. Pseudomonas significantly decreased in lesional and non-lesional skin of treatment responders. These results suggest that skin microbiome alterations after UVB treatment could be related to treatment and treatment response.